6m2+12m=0

Factor 6m out of 6m2.

6m(m)+12m=0

Factor 6m out of 12m.

6m(m)+6m(2)=0

Factor 6m out of 6m(m)+6m(2).

6m(m+2)=0

6m(m+2)=0

Divide each term in 6m(m+2)=0 by 6.

6m(m+2)6=06

Simplify 6m(m+2)6.

Cancel the common factor of 6.

Cancel the common factor.

6m(m+2)6=06

Divide m(m+2) by 1.

m(m+2)=06

m(m+2)=06

Apply the distributive property.

m⋅m+m⋅2=06

Simplify the expression.

Multiply m by m.

m2+m⋅2=06

Move 2 to the left of m.

m2+2m=06

m2+2m=06

m2+2m=06

Divide 0 by 6.

m2+2m=0

m2+2m=0

Factor m out of m2.

m⋅m+2m=0

Factor m out of 2m.

m⋅m+m⋅2=0

Factor m out of m⋅m+m⋅2.

m(m+2)=0

m(m+2)=0

If any individual factor on the left side of the equation is equal to 0, the entire expression will be equal to 0.

m=0

m+2=0

Set the first factor equal to 0.

m=0

Set the next factor equal to 0.

m+2=0

Subtract 2 from both sides of the equation.

m=-2

m=-2

The final solution is all the values that make m(m+2)=0 true.

m=0,-2

Solve for m 6m^2+12m=0